The dynamics of police regulation of sexual abuse of children in South Africa: the case of Grahamstown, Eastern Cape - Van Blerk, Natasha (Rhodes University, Faculty of Humanities, Department of Sociology, 2016)
This thesis investigates the current legislation and police protocols set in South Africa, specifically regarding their adequacy in protecting the country's children from sexual abuse. It focuses on relevant legislative provisions and protocols, on sexual abuse of children and on an empirical study conducted amongst a variety of officials who represent the South African legislation at different levels. Trends, developments and problems are analysed and brought forward to raise an awareness on the severity of the issue of child sexual abuse. In addition, this thesis explores how the diversity within the community of Grahamstown, South Africa, should be considered to a higher degree in the legislation. There is a clear indication of a prevalent patriarchal hierarchy within the community which, in reality, makes women and children more vulnerable to sexual abuse. The methods used in this thesis involves purposive sampling, which led to one on one interviews between the researcher and participant. Thisthesis concludes with confirmation of the hypothesis whereby the South African legislation is not adequately protecting the rights of children in regards to sexual abuse. However, to fully adapt the legislation and make it as versatile and as effective the State hopes it to be, it is necessary to understand the society's perception on women and children and to rectify it. As difficult as this may sound, it all begins with a strong and influential government.
Keywords: Uncatalogued